Fluoroscopic-guided insertion of self-expanding metal stents for malignant gastroduodenal outlet obstruction: immediate results and clinical outcomes. (November 2015) - Diamantopoulos, Athanasios; Sabharwal, Tarun; Katsanos, Konstantinos; Krokidis, Miltiadis; Adam, Andreas
Background: Application of self-expanding metal stents (SEMS) to treat patients suffering from malignant gastroduodenal outlet obstruction (GDOO) is today considered a well-recognized palliative treatment. Use of SEMS has emerged as an attractive alternative to surgical treatment of such patients. Purpose: To report the immediate and the mid-term clinical outcomes from a series of consecutive patients treated with exclusively fluoroscopic-guided insertion of SEMS. Material and Methods: This was a retrospective study including patients suffering from GDOO that were either ineligible for or unwilling to undergo surgery. Patients with potentially curable disease, uncorrectable coagulopathy, gastrointestinal perforation, sepsis, presence of distal small bowel obstruction, and bowel ischemia were excluded. Technical success, clinical success, and major complications were calculated. In addition, stent migration, stent re-obstruction, restenosis, and overall re-interventions due to recurrent symptoms were considered. Kaplan-Meier survival analysis was used for patient survival estimation while both bivariable and multivariable analysis were performed to identify any independent predictors of outcomes. Results: Fifty-one patients, (mean age, 63.73 ± 15.62 years) met the study's criteria and were included in the final analysis. Technical and clinical success were 90.19% ( n = 46/51) and 91.30% ( n = 42/46), respectively. Major complications rate was 3.92%. Stent migration was noted in four cases. Restenosis and re-obstruction rates were 19.57% and 10.87%, respectively. No cases of peri-procedural mortality were noted, while Kaplan-Meier estimates for 1- and 2-year survival were 16.8% and 7.2%, respectively. Clinically successful cases and patients with primary GI tumor were related with more favorable survival compared to unsuccessful and patients suffering from GDOO due to extrinsic compression by neoplastic or lymph node disease. Conclusion: Exclusively fluoroscopically inserted SEMS for GDOO is safe and highly effective method for palliative treatment.